2022
DOI: 10.1186/s13062-022-00338-6
|View full text |Cite
|
Sign up to set email alerts
|

Alamandine alleviated heart failure and fibrosis in myocardial infarction mice

Abstract: Alamandine (Ala) is the newest identified peptide of the renin-angiotensin system and has protective effect on myocyte hypertrophy. However, it is still unclear whether Ala can alleviate heart failure (HF). The aim of this study was to explore the effects of Ala on HF and the related cardiac fibrosis, and to probe the mechanism. HF model was induced by myocardial infarction (MI) in mice. Four weeks after MI, Ala was administrated by intraperitoneal injection for two weeks. Ala injection significantly improved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 96 publications
0
8
0
Order By: Relevance
“…It is worthy to highlight that the treatment of cardiomyocytes derived from the hypertensive rat TGR (mREN2)27 with alamandine promoted the opposite effects, enhancing contractility, promoting the phosphorylation of PLN on Thr-17 and a higher Ca 2+ transient and accelerated Ca 2+ reuptake 65 . In addition, the alamandine treatment of failing hearts due to myocardial infarction reduced oxidative stress and reverted the cardiac damage caused by ischemia/reperfusion, increasing ejection fraction and fractional shortening 66 .…”
Section: Discussionmentioning
confidence: 99%
“…It is worthy to highlight that the treatment of cardiomyocytes derived from the hypertensive rat TGR (mREN2)27 with alamandine promoted the opposite effects, enhancing contractility, promoting the phosphorylation of PLN on Thr-17 and a higher Ca 2+ transient and accelerated Ca 2+ reuptake 65 . In addition, the alamandine treatment of failing hearts due to myocardial infarction reduced oxidative stress and reverted the cardiac damage caused by ischemia/reperfusion, increasing ejection fraction and fractional shortening 66 .…”
Section: Discussionmentioning
confidence: 99%
“…116 A study finds that Alamandine, the newest identified peptide of the renin-angiotensin system, attenuates myocardial oxidative stress and inflammatory responses and prevents myocardial lesions in a DM mouse model. 117 Captopril, an ACEI inhibitor, improved end-diastolic pressure elevation and inhibited myocardial fibrosis in spontaneous DM rats after treatment for 4 months, thus playing a preventive role in DCM. 118 Although ACEIs are generally well-tolerated and have no significant immediate side effects, some studies suggest that reducing Ang II production may lead to adverse effects such as hypotension, acute renal failure, and hyperkalemia.…”
Section: Raas Inhibitors Function As Hypotensive Agents By Inhibitingmentioning
confidence: 98%
“…Experimental studies suggest that RAAS inhibitors may prevent DCM by inhibiting cardiac‐specific NF‐κB signaling 116 . A study finds that Alamandine, the newest identified peptide of the renin‐angiotensin system, attenuates myocardial oxidative stress and inflammatory responses and prevents myocardial lesions in a DM mouse model 117 . Captopril, an ACEI inhibitor, improved end‐diastolic pressure elevation and inhibited myocardial fibrosis in spontaneous DM rats after treatment for 4 months, thus playing a preventive role in DCM 118 …”
Section: Recent Advances In Treatment Researchmentioning
confidence: 99%
“…In a rat model of cardiac ischemia-reperfusion injury, the administration of this peptide reduced the presence of fibrotic markers, increasing the phosphorylation levels of ERK and JNK, while NF-κB decreased ( Song et al, 2019 ). Another mechanism associated with the effects of alamandine was observed in liver and lung, where the peptide attenuated the presence of fibrosis by attenuating autophagy activated by ROS-dependent reactive oxygen species ( Huang et al, 2020 ; Gong et al, 2022 ; Zhao et al, 2022 ). ( Figure 3 ).…”
Section: The Renin-angiotensin System and Its Counter-regulatory Armmentioning
confidence: 99%